IHRM: A Gateway for Nepalese Human Resource for Global Competitive Market - Pandey, Kashiraj (Bodhi: An Interdisciplinary Journal, 2010)
This paper reviews how the concept of International Human Resource Management (IHRM) has opened a gateway for Nepalese Human Resource (HR) in global market. When the world has become a global village, our investment in education and knowledge industry as business by preparing graduates with need based courses for the emerging global market will have great advantage for the country, the individual, and it further contributes in international job market. DOI: 10.3126/bodhi.v2i1.2871 Bodhi Vol.2(1) 2008 p.196-204